<h3>
Answer:</h3>
![\displaystyle x^{\frac{2}{3}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D)
<h3>
Step-by-step explanation:</h3>
The rules of exponents tell you ...
... (a^b)(a^c) = a^(b+c) . . . . . . applies inside parentheses
... (a^b)^c = a^(b·c) . . . . . . . . applies to the overall expression
The Order of Operations tells you to evaluate inside parentheses first. Doing that, you have ...
... x^(4/3)·x^(2/3) = x^((4+2)/3) = x^2
Now, you have ...
... (x^2)^(1/3)
and the rule of exponents tells you to multiply the exponents.
... = x^(2·1/3) = x^(2/3)
Answer:
mhuaaa
Step-by-step explanation:
papapapapapapapapa
Answer:
x=0.6
Step-by-step explanation:
f(×)=3x-2 , 0=3x-2
The two limits when x tends to zero are:
![\lim_{x \to \ 0^-} f(x) = 1\\\\ \lim_{x \to \ 0^+} f(x) = 0](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%20%5C%200%5E-%7D%20%20f%28x%29%20%3D%201%5C%5C%5C%5C%20%5Clim_%7Bx%20%5Cto%20%5C%200%5E%2B%7D%20%20f%28x%29%20%3D%200)
<h3 /><h3>How to get the limits when x tends to zero?</h3>
Notice that we have a jump at x = 0.
Then we can take two limits, one going from the negative side (where we will go along the blue line)
And other from the positive side (where we go along the orange line).
We will get:
![\lim_{x \to \ 0^-} f(x) = 1\\\\ \lim_{x \to \ 0^+} f(x) = 0](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%20%5C%200%5E-%7D%20%20f%28x%29%20%3D%201%5C%5C%5C%5C%20%5Clim_%7Bx%20%5Cto%20%5C%200%5E%2B%7D%20%20f%28x%29%20%3D%200)
Notice that the two limits are different, that means that the function is not a continuous function.
If you want to learn more about limits:
brainly.com/question/5313449
#SPJ1